1980
DOI: 10.1111/j.1365-2133.1980.tb06595.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial acrogeria (Gottron)

Abstract: A mother and her oldest son suffering from acrogeria are described; in the mother the disease was complicated by elastosis perforans serpiginosa. Microscopic and ultramicroscopic details are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 11 publications
1
25
0
1
Order By: Relevance
“…Nail changes include atrophy and thickening which were absent in our patient. 8 In the skin histopathology, there is atrophy of the dermis and subcutis. The collagen fibres are loose and dispersed, while the elastic fibres are always fragmented.…”
Section: Discussionmentioning
confidence: 99%
“…Nail changes include atrophy and thickening which were absent in our patient. 8 In the skin histopathology, there is atrophy of the dermis and subcutis. The collagen fibres are loose and dispersed, while the elastic fibres are always fragmented.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome forms its own clinical entity with atrophic acral skin which reaches about 5 cm to the distal extremities, mottled hyperpigmentation of the skin, thickened nails, micrognathia and atrophic skin on the tip of the nose. Most of the patients described so far show a rather similar clinical syndrome with little het erogeneity of the symptoms [3,4,6,[8][9][10][21][22][23][24][25][26][27][28][29]. In some cases formation of ugly scars, and seldom bruising, belongs also to the picture of acrogeria.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes the differentiation between acrogeria and early-onset meta geria is difficult; it has been suggested that metageria is an extreme variant of acrogeria. In fact, both of these syndromes have been found in the same family [9], Detailed infor mation of more patients and families is needed to further characterize the clinical features as well as the mode of inheritance which has remained unclear because only 2 familial cases of acrogeria have been described so far [4,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations